SAT0410 Hla-b27 role in ankylosing spondylitis phenotype: results from the regisponser database. (15th June 2017) - Arevalo, M; Font, P; Moreno, M; Ruiz, D; Castro, M; Carreto, P; Larrosa, M; Collantes, E; Gratacόs, J
Abstract : Objectives: To assess if there are different phenotypical patterns of Ankylosing Spondylitis (AS) patients depending on the positivity or negativity of HLAB27. Methods: This is a multicentric, observational, transversal and descriptive study of AS patients from the spanish database REGISPONSER. We compared HLAB27 positive and HLAB27 negative patients regarding clinical and demographical data, disease activity and structural damage. In order to assess disease activity we used the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and acute phase reactants (VSG and PCR). Functional disability was measured by Bath Ankylosing Spondylitis Functional Index (BASFI), and structural damage by Bath Ankylosing Spondylitis Radiology Score (BASRI). For qualitative variables we used the Chi square test and for quantitative ones the t test. An univariate and multivariate comparative analyisis was performed, in order to define which variables were related to the negativity or positivity of HLAB27. Results: Data of 1235 AS pacients were analysed. Of them 1029 (83.3%) were HLAB27 positive and 206 (17.7%) HLAB27 negative. 924 (74.8%) were men. AS patients with HLAB27+ presented significantly more familiar history of spondyloarhritis (p=0.002), were younger (p=0.012) and had earlier disease onset and disease diagnosis (p<0.001), with a longer disease duration (p=0.037) and a trend to a higher percentage of uveitis compared to those with HLAB27-. On the other hand, AS patients with HLAB27- also presented significantly more peripheral arthritis (p=0.0022), dactylitis (p=0.001) and extraarticular manifestations (psoriasis, palmoplantar pustulosis, inflammatory bowel disease (IBD) and balanitis (p<0.001)) compared with those of HLAB27+. AS patients with HLAB27- also presented higher scores of BASDAI and BASFI (p=0.047 and p=0.005 respectively). The study didn't show differences between both groups of patients regarding sex distribution, axial manifestations, enthesitis nor radiological damage (assessed by BASRI). In the multivariate analysis, the family history of spondyloarthritis (OR 2.10, IC95% 1.27–3.49, p=0.004), the age at diagnosis (OR 0.97, IC95% 0.96–0.98, p<0.001), the presence of dactylitis (OR 0.16, IC95% 0.05–0.56, p=0.004), extraarticular manifestation specially IBD (OR 0.22, IC95% 0.12–0.40, p<0.001) and peripheral arthritis (OR 0.53, IC95% 0.32–0.89, p=0.016) were the variables independently associated with the presence of HLAB27. Conclusions: The presence of HLAB27 in AS patients is associated to an earlier disease onset, a higher frequency of familiar history of spondyloarthritis, and a lower frequency of dactylitis, extraarticular manifestations and peripheral arthritis. Disclosure of Interest: None declared